A survey of thickened fluid prescribing and monitoring practices of Australian health professionals. Issue 5 (9th May 2014) - Murray, Jo; Doeltgen, Sebastian; Miller, Michelle; Scholten, Ingrid
Abstract Rationale, aims and objectives This study aimed to describe (1) how thickened fluids are supplied to clients with dysphagia; (2) how clients' consumption of thickened fluids and hydration status is monitored; and (3) the impact of institutional factors on thickened fluid intake and hydration in Australian health care settings. Methods Speech pathologists, dietitians and nurses working in Australian health care settings were asked to voluntarily participate in an online survey that was advertised through their respective professional associations. The questions required a self‐report of their practice with respect to thickened fluids. Results Few health care facilities (17%) monitored thickened fluid consumption routinely even though, in the opinion of 51% the respondents, clients on thickened fluids at their facility do not drink enough. Palatability of the thickened fluid products and patients' dependence on others for drinking were thought to have a major impact on fluid intake. Respondents also highlighted institutional factors such as inadequate assistance from staff and inconsistent systems for monitoring fluid intake and signs of dehydration. The most common way to address inadequate intake was for nurses to 'push fluids' (87%). Free water protocols were used only 14% of the time and setting small oral fluid targets throughout the day was the least common strategy (11%). Conclusions There is a need for Australian health care facilities to educate all clinical staff about the risks of dehydration and develop clinical pathways for clients with dysphagia, which include routine monitoring of oral fluid consumption and dehydration and timely intervention.